Teknik Sosiodrama Untuk Meningkatkan Keterampilan Sosial Pada Siswa - Eka Aryani; Palasara Brahmani Laras (STKIP Andi Matappa, 2022)
The research is based on the social skills of the X grade students of SMA Insan Cendekia which are quite low. This study aims to improve the social skills of class X students of SMA Insan Cendekia through sociodrama techniques. This research uses the type of action research (action research). The type of action taken is a sociodrama technique. Data collection methods used are scale and observation. The research instrument used a social skills scale and observation guidelines. The data analysis used in this research is quantitative and qualitative data analysi. The results showed that sociodrama could improve the social skills of class X students of SMA Insan Cendekia. The pre-action was carried out by spreading the scale, the data obtained, the students' social skills were still low with an average pre-test score of 116.38. In the first sociodrama, the average score of post-test I of students increased to 135.18 in the medium category. In the second sociodrama, the average post-test II score of students increased to 161.68 in the high category but had not yet reached the target. In the third sociodrama, the average post-test III score of students increased to 174.28 in the high category and had reached the target. These results were also strengthened by observations of subjects who showed increased social skills from the pre-test which was indicated by students being able to express opinions aloud, able to manage emotions well, able to get along with all friends, and be able to behave assertively.